2018
DOI: 10.1016/j.jid.2018.03.808
|View full text |Cite
|
Sign up to set email alerts
|

798 Biallelic COL7A1 editing in iPSCs via CRISPR/Cas9 for recessive dystrophic epidermolysis bullosa mutations

Abstract: The routine diagnosis of heritable skin and connective tissue disorders is complicated by the fact that in this group of disorders, clinical manifestations may result from genetic or phenotypic heterogeneity and the existence of new genes and/or novel disease subtypes. Autozygosity mapping (AM) has been proven to be a useful adjunct in the molecular diagnosis of homozygous autosomal recessive (AR) diseases. We investigated the utility of AM for the molecular diagnosis of heterogeneous AR disorders, using epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Followed by this, from gene-corrected iPSCs, 3-dimensional human skin equivalents (HSEs) were generated and differentiated into keratinocytes (KCs) and fibroblasts (FBs), and grafted into immunodeficient mice, which showed wild-type expression of COL7A1 and restored anchoring fibrils with no evident off-targets activity or other safety concern. 51 Similar approaches can be implemented in corneal dystrophies as well, where patient-derived iPSC could be generated and corrected for its defective mutation using CRISPR tool followed by its differentiation into endothelial cells, which can be surgically grafted in patients cornea for the rescue of disease phenotype. Interestingly, in 1 study, it was shown that dental pulp contains a population of adult stem cells known as DPSc, that can be harvested from third molars with the capability to differentiate into corneal keratocytes.…”
Section: Crispr Homology End-joining Mechanism and Applicationsmentioning
confidence: 99%
“…Followed by this, from gene-corrected iPSCs, 3-dimensional human skin equivalents (HSEs) were generated and differentiated into keratinocytes (KCs) and fibroblasts (FBs), and grafted into immunodeficient mice, which showed wild-type expression of COL7A1 and restored anchoring fibrils with no evident off-targets activity or other safety concern. 51 Similar approaches can be implemented in corneal dystrophies as well, where patient-derived iPSC could be generated and corrected for its defective mutation using CRISPR tool followed by its differentiation into endothelial cells, which can be surgically grafted in patients cornea for the rescue of disease phenotype. Interestingly, in 1 study, it was shown that dental pulp contains a population of adult stem cells known as DPSc, that can be harvested from third molars with the capability to differentiate into corneal keratocytes.…”
Section: Crispr Homology End-joining Mechanism and Applicationsmentioning
confidence: 99%
“…For example, genetically modified autologous epidermal cells could provide a lasting treatment for vesicular skin diseases. Several studies have shown that it is possible to correct epidermolysis bullosa, a genetic skin disorder, by CRISPR/Cas9-based targeted genome editing (Itoh et al, 2011;Hirsch et al, 2017;Jacków et al, 2019). hiPSCs can become ideal sources of cells for generating skin organoids.…”
Section: The Applications Of Multifunctional Skin Organoidsmentioning
confidence: 99%
“…Additional efficiency can be gained by optimizing both, the format and the delivery of the gene-editing molecules. Currently, electroporation of COL7A1-specific RNPs together with single-stranded oligonucleotide HDR templates have resulted in the highest repair efficiencies [34].…”
Section: Gene Editing Strategies For Epidermolysis Bullosamentioning
confidence: 99%
“…The application of HDR-based approaches to the correction of patient-derived induced pluripotent stem cells (iPSCs) further increases the range of therapeutic options for patients, especially as the isolation of epidermal holoclones can be a limiting factor [14,34]. Pre-clinical studies using corrected iPSCs, that were then differentiated into keratinocytes and fibroblasts, and used to generate three-dimensional skin equivalents (HSEs) on the backs of immunodeficient mice, showed normal type VII collagen expression and restored anchoring fibrils [34]. Alternative strategies, not based on homology-directed repair, comprise base editing, which has proven to be a suitable option for correcting pathogenic mutations in RDEB [36].…”
Section: Gene Editing Strategies For Epidermolysis Bullosamentioning
confidence: 99%